A giant squamous cell carcinoma of the skin of the thoracic wall: a case report and review of the literature - Evangelos P. Misiakos; Vasileia Damaskou; Anna Koumarianou; Alina-Roxani Gouloumi; Paul Patapis; Nick Zavras; Anastasios Machairas (Journal of Medical Case Reports, 2017)
Abstract Background We report a case of a 48-year-old white woman who presented with a huge cutaneous protruding tumor of the thoracic wall below her left breast. Case presentation The lesion was excised with clear margins from the adjacent skin, and subcutaneous tissue was left to heal with second intention. A histological examination of the surgical specimen revealed a well-differentiated infiltrative cutaneous squamous cell carcinoma. Our patient neglected to attend our Oncological Department to receive chemotherapy. Today, 12 months after surgery, she is alive and without evidence of disease recurrence. Conclusions Cutaneous squamous cell carcinoma can reach a huge size if left untreated. Surgery is the primary mode of treatment, followed by chemotherapy if applicable.